2018
DOI: 10.1007/s12560-018-9357-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A Virus, Hepatitis E Virus, and Rotavirus in Foods of Animal Origin Traded at the Borders of Brazil, Argentina, and Uruguay

Abstract: The aim of this study was to investigate hepatitis A virus (HAV), hepatitis E (HEV), and rotavirus (RV) in fresh and processed meat traded on the border of Brazil with Argentina and Uruguay. In total, 159 samples of raw and processed foods of animal origin were collected in Paso de los Libres, Argentina (n = 53 raw meat, n = 24 processed meat) and Rivera, Uruguay (n = 55 raw meat, n = 18 processed meat), or were seized by the Brazilian International Agricultural Surveillance System-VIGIAGRO (Brazil-Argentina b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…Regarding the HEV contamination of meat and meat products derived from swine and other animals ( Table 2 ), HEV RNA was detected in 36% of the pig pâtés and blood sausages (morcilla) derived from pork [ 76 ]. In another study, no HEV was detected either in pig processed meats such as mortadella, sausage, salami, ham, and pate, or in the raw meat of bovine, swine, chicken, and capybara [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the HEV contamination of meat and meat products derived from swine and other animals ( Table 2 ), HEV RNA was detected in 36% of the pig pâtés and blood sausages (morcilla) derived from pork [ 76 ]. In another study, no HEV was detected either in pig processed meats such as mortadella, sausage, salami, ham, and pate, or in the raw meat of bovine, swine, chicken, and capybara [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, various frozen berries, frozen diced potatoes and frozen diced apple were tested as positive in China (2Á8% of total) (Fang et al 2016), as well as strawberries (0Á001%) in South Korea (Shin et al 2019). Of note, a recent study reported that the 18% of raw and processed foods of animal origin traded in Brazilian borders were tested positive for HAV (Pereira et al 2018). In Australia, the prevalence of HAV in berries and leafy greens at retail was estimated to be <2%, with no virus detected in produce during the survey.…”
Section: Prevalence Levels and Risk Associated With Hav In Foodsmentioning
confidence: 99%
“…Of note, a recent study reported that the 18% of raw and processed foods of animal origin traded in Brazilian borders were tested positive for HAV (Pereira et al . 2018). In Australia, the prevalence of HAV in berries and leafy greens at retail was estimated to be <2%, with no virus detected in produce during the survey.…”
Section: Hav Detection In Foodmentioning
confidence: 99%
“…In relation to viral infections, inadequate nutrition could lead to malnourishment (understood as undernutrition or overweight/obesity) and increase the risk of infections [ 184 ], including influenza virus and SARS-CoV-2 [ 185 ]. Diets rich in ultra-processed foods can cause vitamin and mineral deficiencies and, consequently, alter the redox and inflammation status with consequences on the immune response; this may explain a higher susceptibility to some pathogens such as HIV [ 186 ], hepatitis virus [ 187 ] and SARS-CoV-2 under these circumstances [ 188 ].…”
Section: Impact Of Ultra-processed Foods In the Setting Of Viral Infections During Pregnancymentioning
confidence: 99%